PENGARUH METODE PEMBELAJARAN DRILL AND PRACTICE DAN DEMONSTRASI TERHADAP KEMAMPUAN LOMPAT JANGKIT DILIHAT DARI DAYA LEDAK OTOT TUNGKAI (Studi Eksperimen Pada Mata Pelajaran PJOK Kelas X SMA Negeri 1 Lahat) - Bambang Hermawan; Turdjai Turdjai (UNIB Press, 2020)
This study aims to determine the effect of the Learning Method and Leg Muscle Explosion Power on Outbreak Skill Ability. The design used in this study was an experimental squasi with a 2 x 2 factorial design. The study population was all students of class X MIPA SMA Negeri 1 Lahat in the 2019-2020 Academic Year consisting of 4 classes. The class that was used as the sample of the experimental group was Class X MIPA 1 and the control class was Class X MIPA 2. The sample selection was carried out using a purposive random sampling technique. The collected data is processed statistically using a two-way variance (anava) analysis technique. The results showed that: (1) the jumping ability of students learning with the Drill and Practice learning method was higher than the jumping ability of students learning with the learning method Demonstration (2) the jumping ability of students who studied with higher leg muscle explosive power was higher than the jumping ability of students who learn with low limb muscle explosive power (3) There is no interaction between learning methods and leg muscle explosive power to jumping ability